IMPLEMENTASI DATA MINING PADA PENJUALAN MENGGUNAKAN ALGORITMA APRIORI - aritonang, josua; Saragih, Saut (Computer Science and Industrial Engineering, 2022)
The development of information technology, the application of data mining has been applied in various fields, such as fields in business or trade. The purpose of this study is to find a comprehensive way unorganized sales data so that it can provide information on product stock at PT Selatan Indobatam Mandiri and find out how the company can manage transaction data information easily so it can be used as company information by implementing data mining using a priori algorithms via Tanagra. Tanagra is free software for academic and research use. This course covers many data mining techniques, from data mining analysis to statistical learning, from machine learning to databases.